1996
DOI: 10.1002/(sici)1097-0215(19960126)65:3<389::aid-ijc19>3.0.co;2-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of combination of suboptimal concentrations of P-glycoprotein blockers on the proliferation ofMDR1 gene expressing cells

Abstract: Pharmacologically active in vivo doses of P-glycoprotein (Pgp) blockers, specifically verapamil, Cremophor EL and PSC833 cause toxicity in addition to that from the concomitantly used cancer chemotherapeutic drugs. It was shown before that these blockers cause different types of toxicities in vivo. We found that these 3 chemically distinct Pgp blockers exert different biophysical effects on the membranes of LIZ10 MDR cells. They also affect the general metabolism of these cells differently, but all block affin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

1997
1997
2004
2004

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…Bennis et al (35) reported that combinations of verapamil and quinine could act synergistically on MDR; verapamil acting mostly on Pgp‐mediated drug efflux and quinine acting additionally on subcellular distribution of the drugs. Hwang et al (23) reported similar results in combining verapamil with Cremophor EL or PSC833, which were demonstrated to act on the plasma membrane biophysical status. On another hand, MRP modulators such as probenecid were found to restore alteration of the subcellular distribution of anthracyclines in MRP‐overexpressing cell lines but not in Pgp‐overexpressing cell lines (36).…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Bennis et al (35) reported that combinations of verapamil and quinine could act synergistically on MDR; verapamil acting mostly on Pgp‐mediated drug efflux and quinine acting additionally on subcellular distribution of the drugs. Hwang et al (23) reported similar results in combining verapamil with Cremophor EL or PSC833, which were demonstrated to act on the plasma membrane biophysical status. On another hand, MRP modulators such as probenecid were found to restore alteration of the subcellular distribution of anthracyclines in MRP‐overexpressing cell lines but not in Pgp‐overexpressing cell lines (36).…”
Section: Discussionmentioning
confidence: 83%
“…Recently, using fluorescence microscopy colocalization image analysis, we reported that organelles involved in daunorubicin intracellular sequestration in MCF7 DXR cell line were Golgi vesicles (18). In other models, biophysical alteration of the plasma membrane (23, 34) was reported to be implicated in the multidrug resistance phenotype. Therefore, it appeared interesting to evaluate associations of Pgp inhibitors that could act additionally on different subcellular mechanisms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The anionic polymer–SLN system in this work has been demonstrated to possess a relatively nonspecific nature of ionic complexation, which allows loading of flexible combinations of antineoplastic agents and chemosensitizers, for example, DOX and VER, without noticeable alteration of release rates. Because the coadministration of multiple chemosensitizers at suboptimal levels is, in fact, more effective and causes less adverse effects,10 the current system, which is able to deliver multiple chemosensitizers, for example, QS, VER, and Tween‐80®, in a single SLN, may provide similar or stronger therapeutic advantages as well.…”
Section: Discussionmentioning
confidence: 99%
“…To overcome the shortcomings of conventional cancer chemotherapy such as a low therapeutic index and the emergence of the multidrug resistance (MDR) phenotype,1–3 a variety of approaches have been developed. These include the use of cytotoxic drugs in combination, coadministration of chemosensitizers such as the inhibitors of cellular drug‐efflux activities of P‐glycoprotein (P‐gp), or multidrug resistance‐associated protein (MRP) for the reversal of MDR,4–7 and combinational use of chemosensitizers for synergistic therapeutic activities 8–10. Each of these approaches shows some promise as well as limitations.…”
Section: Introductionmentioning
confidence: 99%